DNA Damage and Survival Time Course of Deinococcal Cell Pellets During 3 Years of Exposure to Outer Space - Kawaguchi, Yuko; Shibuya, Mio; Kinoshita, Iori; Yatabe, Jun; Narumi, Issay; Shibata, Hiromi; Hayashi, Risako; Fujiwara, Daisuke; Murano, Yuka; Hashimoto, Hirofumi; Imai, Eiichi; Kodaira, Satoshi; et al. (Frontiers in Microbiology, 2020)
The hypothesis called "panspermia" proposes an interplanetary transfer of life. Experiments have exposed extremophilic organisms to outer space to test microbe survivability and panspermia hypothesis. Microbes inside shielding material with sufficient thickness to protect them from UVirradiation can survive in space. This process has been called "lithopanspermia," meaning rocky panspermia. We previously proposed sub-millimeter cell pellets (aggregates) could survive in the harsh space environment based on the on-ground laboratory experiment. To test our hypothesis, we placed dried cell pellets of the radioresistant bacteria Deinococcus spp. in aluminum plate wells in exposure panels attached to the outside of the International Space Station. We exposed the microbial cell pellet with different thickness to space environments. The results indicated the importance of the aggregated form of cells for surviving in harsh space environment. We also analyzed the samples exposed to space from one to three years. The experimental design enabled us to get and extrapolate the survival time course to predict the survival time of D. radiodurans. Dried deinococcal cell pellets of 500-µm thickness were alive after three years of space exposure and repaired DNA damage at cultivation. Thus, cell pellets 1 mm in diameter have sufficient protection from UV and are estimated to endure the space environment from 3 to 8 years, extrapolating the survival curve and considering the illumination efficiency of the space experiment. Comparison of the survival of different DNA